Pemberdayaan Masyarakat Sekitar Taman Hutan Raya Sultan Thaha Syaifuddin Melalui Konsep Wisata Berbasis Alam Edu-Ecotourism - Wulan, Cory; Paiman, Asrizal; Nursanti, Nursanti; Albayudi, Albayudi; Khabibi, Jauhar; Muryunika, Rince (LPPM Universitas Jambi, 2021)
Indonesia is one of the countries that has a large enough forest in the world. However, the size of the forest area is not in line with the concept of sustainable forest management. The rate of deforestation in Indonesia inside and outside forest areas from 2015 to 2019 reached 56,865.3 ha/year. This condition results in erratic climate change. One of the forest areas in Indonesia that contributes to these conditions is the Sultan Thaha Syaifuddin Forest Park. The condition of this area experienced a decline in both quality and quantity, especially in 2015. This conservation area had experienced a forest fire disaster that year. Therefore, at this time the condition of burned area is in a period of succession. However, this succession process does not appear to be managed properly. This can be monitored from the emergence of acacia (Acacia mangium) which is quite a lot in the burned area. Even though this location is endemic to iron wood tree (Eusideroxylon zwgeri). One very important way to improve this condition is to emphasize community participation around the forest park itself. This participation can be in the context of safeguarding, securing, preserving, and developing a long-term management plan for the forest park. One of the community participatory concepts that can be applied in conservation forest areas, is edu-ecotourism nature-based tourism. The community services activity has been carried out well for outreach activities as well as focused group discussions/FGDs. For outreach activities, the results showed that there was an increase in public understanding and knowledge about edu-ecotourism-based nature tourism. Then for the FGD activities, it was found that the community supports ecotourism activities that will be carried out, with the hope that the community can be directly involved in the ecotourism activities. The community also expects direct guidance and direction from the Batanghari Regency Environmental Service.